Nursing of a patient with diabetic peripheral neuropathy combined with lower limb pain treated by appropriate technology of Traditional Chinese Medicine (中医适宜技术治疗糖尿病周围神经病变合并下肢疼痛1例的护理体会) - GUO Huanli (郭换利); FENG Wenying (冯文英); ZHANG Guohong (张国红); ZHAO Jing (赵静); HUAN Yanping (黄砚萍) (中西医结合护理)
This paper summarized the practice of appropriate technology and nursing of Traditional Chinese Medicine in a patient with diabetic peripheral neuropathy combined with lower limb pain. Based on the nursing risk assessment and syndrome differentiation, scraping therapy, Bian-stone hot ironing-massage and Chinese herbal medicine penetration, Chinese medicine foot bath were carried out to relieve the lower limb pain and anxiety of the patient. (本文总结1例中医护理适宜技术治疗糖尿病周围神经病变合并下肢疼痛的护理经验。基于护理评估结果以及辨证分型, 采取刮痧、砭石熨摩中药透入法以及中药足浴护理干预, 明显减轻患者下肢疼痛的症状, 缓解了焦虑情绪。)